Integrasi Teknologi Informasi Dengan Nilai-Nilai Pancasila dan Pada Era Multikulturalisme - Santoso, Rafly Ramadhani; Soesanto, Edy (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Pancasila education is an important approach in developing an understanding of national values and shaping national character in the current era of multiculturalism. This presents an overview of the significance of technology integration in teaching Pancasila values in the era of multiculturalism. Technology integration facilitates access to relevant and high-quality learning materials, whether in the form of text, audio recordings, videos, or interactions that open up opportunities for individuals from various cultural backgrounds to learn independently and collaborate. The integration of technology in Pancasila learning provides an opportunity to enrich the learning experience with a more interesting and interactive approach. The use of multimedia, simulations and educational games in learning allows students to be actively involved and gain a deeper understanding of the values of Pancasila. The variety of cultures, ethnicities, religions, tribes and languages in Indonesia have formed a multicultural country that is recognized by other countries. There are good and bad effects of this diversity. One of the negative impacts is the emergence of differences of opinion, conflict, injustice, difficulties in social integration, and ethnocentrism. Thus, when integrating technology in Pancasila education, ethical challenges and considerations also need to be taken into account. Privacy protection, data security and filtering inappropriate content need to be prioritized as aspects that must be considered in optimizing the use of technology in Pancasila education. So the integration of technology in Pancasila education in the era of multiculturalism carries great potential in increasing the accessibility, relevance and effectiveness of learning Pancasila values.